Assessment of feedback devices for performance monitoring in master`s swimmers - Rodriguez-Gallego, L.; Lopez-Contreras, G.; Garcia, G. A. D.; Cuenza-Fernandez, F. (International Journal of Performance Analysis in Sport, 2023)
In recent years, new portable performance monitoring devices have appeared in swimming. The study aims to establish the current validity of the FORM Goggles, Finis Stopwatch, and the Garmin Swim 2 Watch, for the partial and total times and stroke count (experiment 1; n = 17) and to compare the effect of the devices considered as valid in monitoring the pace of master swimmers (experiment 2; n = 10). The FORM Goggles and the Finis Stopwatch showed good level of agreement and accuracy (Bland Altman plots showed homoscedasticity and in most cases Lin`s concordance correlation coefficient were>0.95, and the error magnitude<0.2 seconds). These systems allow better pace control compared to Garmin Swim 2, with a difference between target and actual time below 1.5 %. However, the results showed that the concurrent feedback provided by FORM Smart Swim Goggles could offer greater advantages than the traditional feedback provided via the Finis Stopwatch at the end of each series, as swimmers were closer to the target time (p < 0.05). In conclusion both the FORM Goggles and the Finis Stopwatch, showed a good validity and could serve for performance monitoring in swimming, allowing the Form Goggles better pace control.